A Real-time Method on Robot with Continuous Trajectory for Low-drift Odometry and Mapping. (June 2020) - Jialong, Gao; Lei, Sun; Xiaojia, Xiang; Zhenyi, Li
Abstract: This paper mainly proposes a real-time method on the robot with a continuous trajectory for low-drift odometry and mapping, by using range measurements from a 3D laser scanner, but without any other external reference. The common problem of the classical simultaneous localization and mapping (SLAM) method based on lidar is that the estimation of position and attitude is prone to jump discontinuity. It is mainly caused by the vulnerable performance of the optimization solver while it is in a complex scene. By adding kinematic and dynamic constraints into optimization function, our method achieves a lower mean square error(MSE) compare with the original one, and it has been tested in an outdoor experiment with only 3.5% MSE in yaw relative to state of the art.